2005
DOI: 10.1086/426608
|View full text |Cite
|
Sign up to set email alerts
|

Feature Complementarity and Assortment in Choice

Abstract: This research argues that the purchase probability from a given choice set is contingent on the complementarity of the features differentiating its options. In particular, two types of features are distinguished: complementary features, which are characterized by the additivity of their utilities, and noncomplementary features, which are characterized by nonadditive utilities. In this context, it is argued that assortments in which options are differentiated by noncomplementary features are likely to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 33 publications
2
28
1
3
Order By: Relevance
“…Other researchers found that beyond just influencing perception, these structural aspects also affect the ease with which relevant information can be retrieved, which in turn affects the quality of the decision (Lee & Lee, 2004) and the motivation to make a choice (Gourville & Soman, 2005;Russo, 1977). With regard to the too-much-choice effect, the similarity between different options and the degree to which different aspects need to be traded off against each other might also be of importance because these aspects have been shown to effect satisfaction, deliberation time, and choice probability (Chernev, 2005;Dhar, 1997;Dhar & Nowlis, 1999;Fasolo, Carmeci, & Misuraca, 2009;Fasolo, McClelland, & Todd, 2007;Hsee & Leclerc, 1998;Redelmeier & Shafir, 1995). Past research on too much choice, including our own experiments, has not controlled for these specific aspects of the structure of an assortment, some of which could help explain the diverging results, so future research should take these factors into account.…”
Section: Assortment Structurementioning
confidence: 99%
“…Other researchers found that beyond just influencing perception, these structural aspects also affect the ease with which relevant information can be retrieved, which in turn affects the quality of the decision (Lee & Lee, 2004) and the motivation to make a choice (Gourville & Soman, 2005;Russo, 1977). With regard to the too-much-choice effect, the similarity between different options and the degree to which different aspects need to be traded off against each other might also be of importance because these aspects have been shown to effect satisfaction, deliberation time, and choice probability (Chernev, 2005;Dhar, 1997;Dhar & Nowlis, 1999;Fasolo, Carmeci, & Misuraca, 2009;Fasolo, McClelland, & Todd, 2007;Hsee & Leclerc, 1998;Redelmeier & Shafir, 1995). Past research on too much choice, including our own experiments, has not controlled for these specific aspects of the structure of an assortment, some of which could help explain the diverging results, so future research should take these factors into account.…”
Section: Assortment Structurementioning
confidence: 99%
“…Past studies have used small assortment size ranging from 2 to 60 options and large assortment from 3 to 300 options. Some studies even used very big e154 sizes for small assortment group (Chernev, 2006;Inbar, Botti, & Hanko, 2011) and very small sizes for large assortment group (Chernev, 2005;Gourville & Soman, 2005;Haynes, 2009;Sela et al, 2009). Interestingly, these studies too reported presence of choice overload for such diverse assortment sizes.…”
Section: Conceptual Overview and Hypothesis Developmentmentioning
confidence: 99%
“…It is not much of a stretch in logic to link product features to this impact on likelihood to purchase. In the context of complementary and non-complementary bundles of product features, Chernev (2005) …”
Section: The Literaturementioning
confidence: 99%